Pandemic-induced healthcare shifts: an observational analysis of maternal and neonatal outcomes in adolescent pregnancies - Grobeisen-Duque, Orly; Villavicencio-Carrisoza, Oscar; Mora-Vargas, Carlos Daniel; Arteaga-Lopez, Carolina Penelope; Martinez-Salazar, Maria Guadalupe; Rosas-Balan, Alejandro; Leon-Juarez, Moises; Flores-Herrera, Hector; Zaga-Clavellina, Veronica; Aguilera-Arreola, Ma Guadalupe; Helguera-Repetto, Addy Cecilia (Frontiers in Medicine, 2024)
Introduction The COVID-19 pandemic caused widespread changes in healthcare delivery, particularly affecting vulnerable populations such as pregnant adolescents. These patients faced additional challenges, including developmental and gestational changes, stress from isolation, and altered healthcare access, which may have impacted the incidence and prevalence of maternal and neonatal complications. This study aims to compare maternal and neonatal outcomes in adolescent pregnancies before and during the pandemic, focusing on how shifts in healthcare delivery influenced these outcomes. Methodology A retrospective cohort study was conducted, including 340 adolescent pregnant patients who received prenatal care at a tertiary care institution. Patients were divided into two groups: pre-pandemic (n = 209) and pandemic (n = 131). Maternal data, including pre-BMI and gestational weight gain (GWG), were collected to evaluate maternal and neonatal outcomes. Statistical analysis was performed using chi-square tests, Fisher’s exact tests, and odds ratio (OR) calculations. Results The pandemic group showed a statistically significant increase in cesarean deliveries (p = 0.002; OR = 1.99) and cervicovaginitis, particularly caused by Ureaplasma spp. Conversely, the pre-pandemic group had higher rates of psychoactive substance use, maternal urinary tract infections, and neonatal transient tachypnea. In the pandemic group, overweight pre-gestational BMI and cervicovaginitis were more prevalent in patients with adequate GWG, while inadequate GWG was associated with an increased risk of urinary tract infection (UTI). A significant association between pre-gestational overweight/obesity and excessive GWG was also observed (p < 0.05). Conclusion The COVID-19 pandemic altered both healthcare delivery and maternal and neonatal outcomes in adolescent pregnancies. Changes in healthcare access, isolation, and shifts in medical management during the pandemic resulted in higher cesarean rates and infection rates among pregnant adolescents. These findings underscore the need for adaptable, resilient healthcare systems capable of maintaining comprehensive care even in the face of global crises. Further studies are needed to explore long-term effects on adolescent maternal and neonatal health.